A generalized monogenic exponential function in ℍ. Issue 11 (2nd November 2019) - Bock, Sebastian
ABSTRACT: The article presents a monogenic exponential function for the hypercomplex function theory of quaternion-valued monogenic functions in a reduced quaternionic variable, which has essential properties analogous to the complex exponential function e z, z ∈ C . In particular, it is shown that the Taylor series of the monogenic exponential function based on a complete orthogonal system of monogenic Appell polynomials also generalizes the corresponding complex series representation in a canonical manner.